2013
DOI: 10.1371/journal.pone.0060151
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of SNP (c.309T>G) in the MDM2 Gene by the Duplex SmartAmp Method

Abstract: BackgroundGenetic polymorphisms in the human MDM2 gene are suggested to be a tumor susceptibility marker and a prognostic factor for cancer. It has been reported that a single nucleotide polymorphism (SNP) c.309T>G in the MDM2 gene attenuates the tumor suppressor activity of p53 and accelerates tumor formation in humans.MethodologyIn this study, to detect the SNP c.309T>G in the MDM2 gene, we have developed a new SNP detection method, named “Duplex SmartAmp,” which enabled us to simultaneously detect both 309T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…This, in turn, attenuates the p53 tumor suppressor pathway and accelerates tumor formation in humans [45]. Asians, including Japanese, have higher frequencies of the 309G allele as compared with African-Americans and Caucasians [46]. It has been reported that this polymorphism in the MDM2 gene is associated with the prognosis for several types of tumors, including lung cancer [47].…”
Section: Discussionmentioning
confidence: 99%
“…This, in turn, attenuates the p53 tumor suppressor pathway and accelerates tumor formation in humans [45]. Asians, including Japanese, have higher frequencies of the 309G allele as compared with African-Americans and Caucasians [46]. It has been reported that this polymorphism in the MDM2 gene is associated with the prognosis for several types of tumors, including lung cancer [47].…”
Section: Discussionmentioning
confidence: 99%
“…product development. A variety of different SNP detection methods have lately been described [169][170][171]. Kawai et al report about a first Influenza A (H1N1) assay, combining both a reverse transcriptase and a SmartAmp amplification in one-step setup.…”
Section: Various Other Methodsmentioning
confidence: 99%
“…The DNA was used for SNP typing of c.309T>G and p53 Arg72Pro polymorphisms. Genotyping of c.309T>G was carried out using the Duplex SmartAmp method as described previously [22]. p53 Arg72Pro was genotyped using polymerase chain reactionrestriction fragment length polymorphism (PCR-RFLP) based on a previous report [23].…”
Section: Snp Genotypingmentioning
confidence: 99%
“…Although our findings need to be validated in prospective studies, c.309T>G would be a useful prognostic marker that is detectable at any stage of diagnosis or treatment and influences the therapeutic strategies. Furthermore, we had already established the Duplex SmartAmp method [22] to detect c.309T>G with a single drop (5 μL) of blood within 40 min from sample collection. If we can make this method more practical, we will detect this SNP more easily and quickly in any clinical situation.…”
Section: Mdm2 Snp309 and Lung Cancer Prognosesmentioning
confidence: 99%